Nurturing national identity: language affirmation through patriotic and children's songs among Indonesian students in Penang - Gia Azizatul Goniyah; Fitri Puji Rahmawati (University of Muhammadiyah Malang, 2026)
This study addresses the challenges of teaching Indonesian to diaspora students who live in multilingual environments and tend to experience language shift toward dominant languages such as Malay and English. The research aims to analyze the use of national songs and Indonesian children’s songs in Indonesian language learning at SB Ami Penang and to identify their effects on students’ linguistic skills and national identity. Using a descriptive qualitative approach, data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman. The findings show that instruction through songs is implemented in four stages—song introduction, group singing, vocabulary enrichment, and language practice—which effectively improve vocabulary mastery, pronunciation accuracy, writing ability, speaking confidence, and long-term memory retention. Songs also help minimize Malay language interference through direct lexical comparison and strengthen students’ national identity. Challenges encountered include the dominance of environmental languages, limited audio facilities, varied student ages, and low familiarity with standard Indonesian vocabulary. These challenges were addressed through visual media, simplified lyric explanations, age-appropriate song selection, and reinforcement activities. Overall, music-based learning is proven to be an effective and contextually relevant strategy for enhancing Indonesian language proficiency and strengthening national identity among diaspora students.